Workshop of International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9cm) at RMC Pakandangan Clinic - Sayati Mandia (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Completeness of BPJS claim documents at the hospital includes service recapitulation and patient support files consisting of a Participant Eligibility Letter (SEP), medical resume, diagnostic statement from the treating doctor, and other proof of service. The BPJS claim process already uses the INA-CBGs program. Payment patterns with INA-CBGs organized by BPJS in hospitals must go through the file verification stage so that BPJS Health verifiers verify service Administration and ensure the suitability of diagnoses and procedures on bills with ICD-10 and ICD-9 codes. In coding patient medical actions/procedures, coders use ICD-9 CM rules to assign medical action codes to the patient's resume sheet. Coding of medical procedures is carried out to provide classification and specific information regarding medical actions grouped based on ICD-9 CM. Based on these problems, the author is interested in holding ICD-9 CM coding training at the RMC Pakandangan Clinic. This community service is important because it will reduce pending claims from PBJS. Objective: This community service aims to provide training related to ICD-9 CM coding and increase knowledge of medical recorders. This community service method is carried out using 3 stages, namely preparation, implementation, and evaluation. This workshop is to provide material regarding the use of ICD-9 CM and provide direct practice in coding ICD-9 CM based on applicable regulations. Results: This Community Service Activity (PKM) was carried out on April 8 2023 at the RMC Pakandangan Clinic, Padang Pariaman. The Community Service activity was attended by 10 participants. From the results of the pre-test and post-test in the ICD-9 CM coding training, there was an increase in understanding of ICD-9CM coding. Conclusion: This Community Service has a positive impact on the understanding of ICD-9 CM coding training participants.